2018
DOI: 10.3390/mi9080389
|View full text |Cite
|
Sign up to set email alerts
|

Glancing Angle Deposition Effect on Structure and Light-Induced Wettability of RF-Sputtered TiO2 Thin Films

Abstract: Crystalline TiO2 films were prepared on unheated glass substrates by radio frequency (RF) reactive magnetron sputtering at normal angle of incidence (a = 0°) and at glancing angle (a = 87°). The effect of the glancing angle on the structure, microstructure, and wetting properties of the films was investigated. The inclination of the substrate led to phase transformation of the deposited films from rutile to either rutile/anatase or anatase, depending on the working pressure. Extreme shadowing at 87° results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It was found that N-doping was successfully achieved by thermal annealing of the as-prepared anodic TNAs in pure NH 3 gas [36]. In addition, N-doped TiO 2 thin films were prepared by sputtering in N 2 gas containing ambient [37,38,39]. Jeon et al [29] successfully developed three-dimensional nanostructured N-doped TiO 2 monolith with enhanced visible light absorption, where the N-doping was obtained by thermal annealing of as-prepared 3D nanostructured TiO 2 with a thin TiN layer coating on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that N-doping was successfully achieved by thermal annealing of the as-prepared anodic TNAs in pure NH 3 gas [36]. In addition, N-doped TiO 2 thin films were prepared by sputtering in N 2 gas containing ambient [37,38,39]. Jeon et al [29] successfully developed three-dimensional nanostructured N-doped TiO 2 monolith with enhanced visible light absorption, where the N-doping was obtained by thermal annealing of as-prepared 3D nanostructured TiO 2 with a thin TiN layer coating on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to photonic films on glass and Si substrates, their fabrication on ARSA (Au/P r –Ge) substrates provided better formation of films due to improved wettability to the substrate. This is commonly observed in film coating on higher roughness substrates, which is made by the oblique angle deposition technique. ,, For quantitative comparison, Figure c shows the CIE coordination converted from the reflectance spectrum in Figure a, showing an enlarged color gamut for 1D PCs on ARSA compared with glass.…”
Section: Resultsmentioning
confidence: 93%
“…This particular thermodynamic limit is affected by the effective supersaturation, which is related to the number of atoms crystallizing (related to f and E ), temperature, and oxygen pressure (which affect bulk stability). , Once a region of the more stable phase nucleates, e.g., 4H in BSMO, the probability of its nucleation in that region immediately becomes preferred (possibly absolute), due to both its inherent bulk stability and its local epitaxial stability upon the preexisting stable phase deposit. , From that thickness onward, the local probabilities of nucleation vary with respect to location depending on the structure of the pre-existing film in the local area, and ultimately the film will convert completely to the stable (4H) phase with increased thickness, with some thickness range of mixed phase. That 40 nm films can be fabricated using iPLD indicates that any single-phase thickness value in rPLD is likely related to a thickness-dependent change in local nucleation probabilities, in a manner that decreases the preference for the epitaxially stabilized metastable phase. …”
Section: Discussionmentioning
confidence: 99%